In Toco Village, Trinidad - (:unkn) unknown (My University, 2009)
This high contrast black and white photograph shows us a little of village life in Toco, Trinidad. A variety of trees and houses line the wide road. They cast shadows on the road in the foreground. On the left at mid-ground is a simple, galvanize roof which is held up with three, straight poles. Concrete steps emanate from this and cascade into the road. On the right the louvered doors of another house can be seen. The rest of the structure is hidden by a gigantic fruit tree. Someone is standing slightly leaned over on the road near the horizon. Behind him is an adult coconut tree with feather-like leaves. All that can be seen of the other houses in the photograph are their Caribbean style roof tops.
Colour: Black and White; Style: Portrait; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Trees--Trinidad and Tobago; Rural villages--Trinidad and Tobago; Rural roads--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Toco; Dwellings--Trinidad and Tobago; Roofs--Trinidad and Tobago; Stairs--Trinidad and Tobago